2020
DOI: 10.2147/opth.s290611
|View full text |Cite
|
Sign up to set email alerts
|

Visian® ICLV4c™ and Artiflex®: Comparative Analysis with the HD Analyser™ and Integration with Subjective Performance and Anatomical Parameters

Abstract: Purpose:To analyze and compare the mid-term objective and subjective performance of two phakic intraocular lenses (PIOLs) -Visian ® ICL™ V4c and Artiflex ® and to correlate those results with anatomical parameters. Patients and Methods: Observational retrospective study including thirty patients (15 for each PIOL) randomly selected from those who underwent bilateral implantation of one of the PIOLs (60 eyes were analysed). Uncorrected and corrected distance visual acuities (UDVA and CDVA), anterior chamber str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…2–4 Both objectively measured light scatter and subjectively evaluated patient questionnaires revealed the excellent optical performance of modern pIOL. 5…”
mentioning
confidence: 99%
“…2–4 Both objectively measured light scatter and subjectively evaluated patient questionnaires revealed the excellent optical performance of modern pIOL. 5…”
mentioning
confidence: 99%
“…They concluded that both the Visian ® ICLV4cTM and the Artiflex ® showed excellent optical performance through the HD Analyzer TM technology, with no statistically significant differences between the 2 types of phakic IOL, despite better UDVA in the Artiflex ® group. 7 While observing the graphics represented on Figures 1-4, concerning the comparison of objective quality of vision parameters between the 3 types of procedures (PRK, FS-LASIK and LASIK), we easily understand that at 1st week all parameters show highly different values in the PRK group. This could explain why these patients experience a slower recovery of visual acuity and visual quality.…”
Section: Discussionmentioning
confidence: 94%
“…They concluded that both the Visian ® ICLV4cTM and the Artiflex ® showed excellent optical performance through the HD Analyzer TM technology, with no statistically significant differences between the 2 types of phakic IOL, despite better UDVA in the Artiflex ® group. 7 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Authors, number of eyes included, follow-up, preoperative SE and instruments used to measure optical quality are shown. Wan et al [ 17 ] had the largest sample of all 17 studies with 137 eyes, and Baptista et al [ 22 ] had the longest follow-up period (38.5 months). Average preoperative SE across all the studies was − 8.90 D, but for individual SE value it ranged from − 4.26 D [ 21 ] to − 14.01 D [ 17 ].…”
Section: Main Textmentioning
confidence: 99%